Bioactive properties: enhancement of hepatoprotective, antioxidant and DNA damage protective effects of golden grey mullet protein hydrolysates against paracetamol toxicity. Issue 41 (26th June 2018) - Bkhairia, Intidhar; Dhibi, Sabah; Nasri, Rim; Elfeki, Abdelfettah; Hfaiyedh, Najla; Ben Amara, Ibtissem; Nasri, Moncef
Abstract : This study was undertaken to examine the hepatoprotective, antioxidant, and DNA damage protective effects of protein hydrolysates from Liza aurata, against paracetamol overdose induced liver injury in Wistar rats. Abstract : This study was undertaken to examine the hepatoprotective, antioxidant, and DNA damage protective effects of protein hydrolysates from Liza aurata, against paracetamol overdose induced liver injury in Wistar rats. L. aurata protein hydrolysates (LAPHs) were mainly constituted by glutamic acid (Glu) and glutamine (Gln) and lysine (Lys). In addition, they contained high amounts of proline (Pro), leucine (Leu) and glycine (Gly). The molecular weight distribution of the hydrolysates was determined by size exclusion chromatography, which analyzed a representative hydrolysate type with a weight range of 3–20 kDa. The hepatoprotective effect of LAPHs against paracetamol liver toxicity was investigated by in vivo assay. Rats received LAPHs daily by gavage, for 45 days. Paracetamol was administrated to rats during the last five days of treatment by intraperitoneal injection. Paracetamol overdose induced marked liver damage in rats was noted by a significant increase in the activities of serum aspartate amino transferase (AST) and alanine amino transferase (ALT), and oxidative stress which was evident from decreased activity of the enzymatic antioxidants (superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx)), and level of glutathione (GSH), and increased concentration of lipid peroxidation products (MDA). Furthermore, paracetamol increased the DNA damage with liver histopathological changes. LAPH pretreatment significantly attenuated paracetamol-induced hepatotoxic effects, including oxidative damage, histopathological lesions, and apoptotic changes in the liver tissue. Interestingly, LAPHs restored the activities of antioxidant enzymes and the level of GSH, ameliorated histological and molecular aspects of liver cells. The present data suggest that paracetamol high-dose plays a crucial role in the oxidative damage and genotoxicity of the liver and therefore, some antioxidants such us LAPHs might be safe as hepatoprotectors. Altogether, our studies provide consistent evidence of the beneficial effect of LAPHs on animals treated with a toxic dose of paracetamol and might encourage clinical trials.